Guarana (Paullinia cupana Kunth), marapuama (Ptychopetalum olacoides Benth.), gentian (Gentiana lutea L.), quassia (Quassia amara L.) and their properties: a brief review (Research, Society and Development, 2022)
The discovery and management of natural resources are essential in the social development process. For thousand years, humanity has been using plants for the most diverse purposes, such as the relief and cure of illnesses. The Brazilian floristic diversity also enabled native communities to acquire and to develop knowledge associated with the usage of numerous plants. This brief literature review aims to survey the properties of four plant species – guarana (Paullinia cupana Kunth), marapuama (Ptychopetalum olacoides Benth.), gentian (Gentiana lutea L.), quassia (Quassia amara L.) – widely used by natives of the Amazon region, especially due to their therapeutic properties. Finally, it is possible to highlight the existence of great potential for furthering research on the revised plant species, especially regard to herbal medicine usage – once these have shown, according to consulted sources, to assist in the most diverse health conditions.